A New User Authentication Protocol for Wireless Sensor Networks Using Elliptic Curves Cryptography - Wenbo Shi; Peng Gong (International Journal of Distributed Sensor Networks)
User authentication in wireless sensor networks (WSNs) is a critical security issue due to their unattended and hostile deployment in the field. Since sensor nodes are equipped with limited computing power, storage, and communication modules, authenticating remote users in such resource-constrained environments is a paramount security concern. To overcome the weaknesses of Yeh et al.'s protocol, we proposed a new authentication protocol for wireless sensor networks using elliptic curves cryptography. The comparisons show that our protocol is more suitable for WSNs.